The geographical indication and its socioeconomic and cultural impacts through the case study of the Corupá region - Siewert, Roseli; Aveni, Alessandro (Revista Coleta Científica, 2020)
The present article lays a brief history of the indication of the source or Geographical Indication (GI) which occurs in several territories in the world, certifying locations and periods in which their protection mechanisms for certain products were initiated. It reports how this process takes place in Brazil and how this Geographical Indications (GI) movement takes place in the State of Santa Catarina through the Cooperation Network. It lastly presents the case study of the socioeconomic and cultural impacts of the GI Region of Corupá.